2006
DOI: 10.1590/s0102-311x2006000200020
|View full text |Cite
|
Sign up to set email alerts
|

The magnitude of intimate partner violence in Brazil: portraits from 15 capital cities and the Federal District

Abstract: This paper concerns the prevalence of intimate partner violence in 15 State capital cities and the Federal District of Brazil. A population-based multi-stage survey in 2002/2003 involved 6,760 15-69-year-old women (respondents). Using the Conflict Tactics Scales--Form R, the overall prevalence of psychological aggression and "minor" and severe physical abuse within couples was 78.3%, 21.5%, and 12.9%, respectively. Prevalence rates varied distinctively between cities. For instance, total physical abuse ranged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
53
4
47

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(109 citation statements)
references
References 27 publications
5
53
4
47
Order By: Relevance
“…With respect to physical intimate partner violence, in the analyses stratified by gender, results showed no significant differences between physical violence reportedly perpetrated only by women or only by men, corroborating the findings of other studies (22,23) . When analysing reciprocal intimate partner violence, the prevalence of minor physical violence identified (9·6 %) was lower than the mean found for fifteen Brazilian state capital cities (21·5 %) in previous studies (20) that evaluated the profile of physical intimate partner violence in Brazil. A similar situation was found for severe physical violence, reported as 4·7 % in Salvador compared with a mean of 12·9 % for the fifteen state capital cities evaluated, with the highest prevalence being found in Belém (22·1 %) (20) .…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…With respect to physical intimate partner violence, in the analyses stratified by gender, results showed no significant differences between physical violence reportedly perpetrated only by women or only by men, corroborating the findings of other studies (22,23) . When analysing reciprocal intimate partner violence, the prevalence of minor physical violence identified (9·6 %) was lower than the mean found for fifteen Brazilian state capital cities (21·5 %) in previous studies (20) that evaluated the profile of physical intimate partner violence in Brazil. A similar situation was found for severe physical violence, reported as 4·7 % in Salvador compared with a mean of 12·9 % for the fifteen state capital cities evaluated, with the highest prevalence being found in Belém (22·1 %) (20) .…”
Section: Discussioncontrasting
confidence: 73%
“…When analysing reciprocal intimate partner violence, the prevalence of minor physical violence identified (9·6 %) was lower than the mean found for fifteen Brazilian state capital cities (21·5 %) in previous studies (20) that evaluated the profile of physical intimate partner violence in Brazil. A similar situation was found for severe physical violence, reported as 4·7 % in Salvador compared with a mean of 12·9 % for the fifteen state capital cities evaluated, with the highest prevalence being found in Belém (22·1 %) (20) . Following the appropriate adjustments, it was found that participants reporting minor (PR = 1·23; 95 % CI 1·12, 1·35) and severe (PR = 1·16; 95 % CI 1·00, 1·34) reciprocal physical violence were more likely to be experiencing household food insecurity, compared with those not reporting physical violence.…”
Section: Discussioncontrasting
confidence: 73%
“…No Brasil, no início dos anos 2000, vários estudos foram realizados sobre prevalência de VPI [4][5][6] . Em estudo de base populacional para estudar a magnitude da violência praticada por mulheres e homens em relacionamentos heterossexuais estáveis, entrevistou 6.760 mulheres de 15-69 anos em 15 capitais do Brasil e o Distrito Federal 4 .…”
Section: Introductionunclassified
“…Em estudo de base populacional para estudar a magnitude da violência praticada por mulheres e homens em relacionamentos heterossexuais estáveis, entrevistou 6.760 mulheres de 15-69 anos em 15 capitais do Brasil e o Distrito Federal 4 . A prevalência de violência psicológica ocorreu em 78,3% dos casais, e a violência física classificada em "menor" e "severa" foi descrita por 21,5% e 12,9% dos casais, respectivamente 4 . Apesar das mulheres também serem agressoras, os escores para violência física foram sempre maiores quando o homem era o agressor 4 .…”
Section: Introductionunclassified
“…Ademais, nenhum dos trabalhos anteriores investiga a relação entre a violência física entre parceiros íntimos e o momento de início do acompanhamento da criança no serviço de saúde, bem como as dimensões envolvidas nesse processo. Diante da grande magnitude das diferentes formas de violência entre parceiros íntimos em nosso país 15 e do reconhecimento de que grande contingente de crianças ainda não frequenta de forma regular aos serviços de saúde 3,4 , a realização de pesquisas que possam avaliar as possíveis repercussões das violências na utilização de serviços pediátricos se torna bastante oportuna. Sendo assim, o objetivo principal deste estudo foi avaliar se a violência entre parceiros íntimos, em particular a violência física entre eles nos primeiros seis meses após o parto, é um fator de risco para o início tardio do acompanhamento da criança em unidades bási-cas de saúde (UBS).…”
Section: Introductionunclassified